Performance Analysis of Total Attenuation Effects and Different Values of Transmitter Power on Bit Error Rate and Signal-To-Noise Ratio for Free Space Optical Communication - Akbari, Mahdi; Olyaee, Saeed (Recent Advances in Electrical & Electronic Engineering, 2022)
Objectives: In this paper, the performance of pulse position modulation (PPM), nonreturn zero modulation (NRZ), and return zero modulation (RZ) at signal-to-noise ratio and bit error rate in free space optical communication is compared. This comparison is performed to obtain the most effective modulation in atmospheric attenuations. Also, the effect of increasing transmitter power on the bit error rate and signal-to-noise ratio is investigated. Methods: Utilizing a light source with a wavelength of 1550 nm, the system is simulated in MATLAB by choosing the Kim data transmission link model with different visibility values of 0- 10 km. The analytical equations of free space optical communications are implemented by selecting appropriate parameters. The effects of weak, moderate, and strong atmospheric attenuation, geometric loss, and different transmitter powers (1-5 mW) on bit error rate and signal-to-noise ratio are investigated for all three modulations. Results: The results show that PPM is the most effective modulation compared to other modulations used in this study and shows a better performance in the mentioned atmospheric attenuation conditions within the given values of bit error rate and signal-to-noise ratio. Conclusion: Modulations with lower average power will perform better than other modulations in bit error rate and signal-to-noise ratio under the same atmospheric attenuation conditions. In PPM modulation, increasing the transmitter power causes more reduction in the bit error rate than other modulations used in this paper. Therefore, using this modulation to optimize the power budget in free space optical communications will be appropriate.
Keywords: signal-to-noise ratio